Hubungan Glaukoma dengan Hipertensi - Muhammad Arsy Kamal Faadhil; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Glaucoma is a group of progressive optic neuropathy characterized by degeneration of retinal ganglion cells and resulting changes in the optic nerve head. Glaucoma can be classified into 2 broad categories: open-angle glaucoma and angle-closure glaucoma. In patients with open-angle glaucoma, there is increased resistance to aqueous outflow through the trabecular meshwork. Conversely, access to drainage pathways is usually obstructed in patients with angle-closure glaucoma. Intraocular pressure can cause mechanical stress and strain on the posterior structures of the eye, especially the lamina cribrosa and the surrounding tissues.Acute open angle glaucomacan manifest itself with pain radiating from the eye, visual disturbances, conjunctival hyperemia, and occasionally nausea and vomiting with a tense, rock-hard globe. This is an ophthalmological emergency that requires immediate treatment to prevent severe eye damage and blindness. In contrast, open-angle glaucoma is usually asymptomatic until it reaches an advanced stage. If there are visual field defects, they are usually not located in the same part of the fields of the two eyes and are therefore well compensated for by binocular vision. Thus, people with open-angle glaucoma generally report no symptoms and many are completely unaware that they have the condition.Several epidemiological studies have reported that an increase in systemic blood pressure is associated with a small increase in intraocular pressure. Individuals with hypertension have a risk of about 1.2 times higher for developing open-angle glaucoma than individuals without hypertension followed by other risk factors, namely age over 40 years, and use of antihypertensive drugs. Patients over 40 years of age, especially those with a history of hypertension, are advised to undergo an eye examination.